RANCANG BANGUN TONGKAT PINTAR TUNANETRA BERBASIS MIKROKONTROLER - Parito, Parito; Diafari Djuni, I Gusti Agung Komang; Gunantara, Nyoman (Jurnal SPEKTRUM, 2021)
Blind part of a community that has limited mobility to the environment in social life. The mobility expected by the visually impaired is not only seen from the social side. We both know that the sense of sight is one of the sources of vital information for humans. Most of the information obtained by humans comes from the sense of sight. The design of this tool will help users avoid objects that are in front, will detect water in the reach of the stick with sound notifications according to sensor readings. In addition, users also get pick-up mobility if something happens on the road by pressing the emergency button on the device, then the device will send a telegram message to the family in the form of the coordinates of the GPS stick location. So that the user of this stick will be easy to find if you need emergency help when you are away from home. From the results of testing the tool as a whole, the Blind Smart Stick can work well, namely it can detect obstacles, and the water in front of it, can issue a warning sound to the user, and can send Telegram messages.